Stress Fallout: How Burnout Fuels Employee Turnover: Dampak Stres: Bagaimana Kelelahan Memicu Perputaran Karyawan - lasmi, Ni Wayan; Putra P, Komang Widhya Sedana (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This study explores the impact of job stress, stress-induced exhaustion, and withdrawal on turnover intention, with a focus on the mediating role of stress-induced exhaustion and withdrawal in the relationship between job stress and turnover intention. Conducted at The Tanis Beach Resort, Nusa Lembongan, the research involved 70 employees selected through purposive sampling from a population of 170, targeting permanent employees with at least two years of experience. Data were collected via questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results reveal that job stress, exhaustion, and withdrawal positively and significantly influence turnover intention. Furthermore, stress-induced exhaustion and withdrawal were found to significantly mediate the relationship between job stress and turnover intention. These findings offer valuable insights for human resource management at The Tanis Beach Resort, suggesting strategies to reduce turnover intention by addressing job stress and fostering a supportive work environment.